1996
DOI: 10.1016/s0031-0182(96)00071-5
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and climatic signals in the oxygen isotopic composition of Eocene-Oligocene equid enamel phosphate

Abstract: Oxygen isotope results for tooth enamel-phosphate (6p) from late Eocene-early Oligocene fossil horses are presented to determine if paleobiologic and paleoclimatologic information is recorded in fossil tooth enamel chemistry. Teeth from jaws of Mesohippus and Miohippus from the White River Formation (or Group) in the western Great Plains are well preserved and have excellent geochronologic control. Although there is clear evidence for post-depositional alteration of the enamel, a hydroxylapatite mineralogy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 44 publications
(72 reference statements)
3
81
0
1
Order By: Relevance
“…Because the timing of tooth growth is fixed within a species, inter-individual variability in the δ 18 O sequences retrieved from enamel ( Figure 1c) is related to variability in the season of birth (Bryant et al, 1996;Fricke and O'Neil, 1996). This variability may be described through the observation of the position of the optimum value of the δ 18 O cycle in the tooth crown (Balasse et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Because the timing of tooth growth is fixed within a species, inter-individual variability in the δ 18 O sequences retrieved from enamel ( Figure 1c) is related to variability in the season of birth (Bryant et al, 1996;Fricke and O'Neil, 1996). This variability may be described through the observation of the position of the optimum value of the δ 18 O cycle in the tooth crown (Balasse et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Based on this result, they showed that the most equid individuals were born in spring for Miocene equids from Nebraska (Bryant et al, 1996a) and Eocene-Oligocene equids from Wyoming and South Dakota (Bryant et al, 1996b). Fricke and O'Neil (1996) observed significant differences in d…”
Section: Measured Dmentioning
confidence: 95%
“…This isotopic signature may be derived from either the phosphate or carbonate compartments of mammalian bioapatite (15). The recovery of phosphate derived δ 18 O was developed originally to access palaeoclimate temperature data stored in fossil mammal teeth (16)(17)(18)(19), whilst other studies have employed carbonate derived δ 18 O (20,21). The drinking water intake of mammals contains δ 18 O values which are derived from average precipitation (rain water), which in turn contributes to ground water values (22,23).…”
Section: Introductionmentioning
confidence: 99%